THE INFLUENCE OF WORK MOTIVATION AND DISCIPLINE ON THE PERFORMANCE OF MAKASSAR CITY EDUCATION OFFICE EMPLOYEES - Ulfa Ramadhani; Muhammad Rusydi; Alfian Rendra Anggoro (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to determine the influence of work motivation and discipline on employee performance at the Makassar City Education Office. This research uses a quantitative type of research, where the sample in this research is employees who work in the Education office. Based on the results of the t-test, it can be concluded that motivation variables have a positive influence on employee performance. This finding was revealed through a comparison between tcount and ttable (3.123 > 1.674) and a significance value of 0.003 < 0.05. Therefore, it can be stated that motivation (X1) has a positive influence on employee performance. Based on the t-test analysis, it is concluded that the work discipline variable has a positive influence on employee performance. This image initer fact is based on a comparison of tcount which is higher than ttable (7.946> 1.674) and a significance value of 0.000 <0.05. Therefore, it can be agreed that work discipline (X2) has a positive impact on employee performance. The results of this research show that motivation has a positive and significant effect on employee performance. This means that due to work motivation, employees at the Makassar City Education Office are motivated to work because there is a need in life that must be met. The results of this research show that discipline has a positive and significant effect on employee performance. This can be interpreted that the higher the employee's work discipline which includes the employee's presence on time, working at the time specified according to the work schedule, the employee's performance level will increase.